Mothers Rearing Behavior and Dental Caries Status of Preschool Children’s Primary Teeth in Tambon Wang Thong, Phitsanulok - Mahachaipongkul, Thanakom (Journal of Health Science of Thailand, 2018)
The purpose of this survey study was to examine the relationship between the caries in primary dentition of preschool children and mothers rearing behaviors, knowledge as well as socio-economic factors. The sample was composed of 100 preschool children aged 2-6 years, accompanied by their mothers, living in Tambon Wang Thong Amphoe Wang Thong, Changwat Phitsanulok. Data were collected during 1-31 October 2007, analyzed and presented in terms of means, percentage and standard deviation. Statistical tests employed were t-test and Pearsonีs Product Moment Correlation coefficient at 0.05 level of significance. The results revealed that 70.0 percent of these children had dental caries with a mean of decayed, missing and filled teeth (dmft) 4.41 teeth. Their mothers had moderate level of appropriate rearing behavior (59 to 90 from 108 marks) with an average score of 78.50. It was found that mothers age, workplace and the knowledge of child rearing had no relationship with their children’s dental caries. Years of education had significantly reversed correlation to preschool children’s dental caries (p < 0.05). Regarding mothers rearing behaviors-feeding, sweet consumption, oral cleaning- it was found that dental caries in primary teeth of these preschool children was correlated with sweet consumption behavior and oral cleaning behavior by their mothers (p < 0.05). Among families socio-economic variables, only the families income per month significantly correlated with preschool children’s dental caries. It is not surprising that the children of highly educated mothers, high family income, low sweet consumption behavior, with good oral cleaning behaviors had good dental health.